Bestiarium : Theatergarten. (München : Rüdiger Schöttle, 1987)
Bach, Michael ; Balkenhol, Stephan ; Fremd, Franz ; Fritsch, Katharina ; Graham, Dan ; Kasseböhmer, Axel ; Kütz, Walter ; Van Ofen, Michael ; Schütte, Thomas ; Wall, Jeff
Bestiarium Theatergarten, Künstlerwerkstatt Lothringer Strasse 13, München, 23.10. - 22.11.1987
boek